Mental Health Status of Healthcare Workers During the Coronavirus Disease 2019 Pandemic: A Survey of Hospitals in Shiraz, Iran: - Heydari, Seyed Taghi; Mani, Arash; Kharazi, Mani; Yousefi, Mohammad Reza; Akbary, Ali; Banakar, Morteza; Molavi Vardanjani, Hossein; Zarei, Leila; Khabaz Shirazi, Mohammad; Bagheri Lankarani, Kamran (Galen Medical Journal, 2023)
Background:Healthcare workers (HCWs) directly or indirectly involved in the coronavirus disease 2019 (COVID-19) treatment process may experience severe mental consequences of the pandemic. Hence, this study aimed to evaluate the mental health status of HCWs in hospitals affiliated with Shiraz University of Medical Sciences, Iran. Materials and Method:This cross-sectional study was performed on 503 HCWs from five hospitals in Shiraz, including one COVID-19 front-line hospital, two COVID-19 second-line hospitals, and two without COVID-19 wards. Then, to assess the levels of anxiety, depression, insomnia, and post-traumatic stress disorder (PTSD) among HCWs, the Persian versions of the Hospital Anxiety and Depression Scale (HADS), Insomnia Severity Index (ISI), and Global Psychotrauma Screen (GPS) questionnaires were placed, respectively. Results:The mean age of participants was 33.94Â±8.26 years, and 252 (50.1%) were females. Anxiety, depression, insomnia, and moderate to high levels of PTSD were observed in 40.4%, 37.8%, 24.5%, and 71% of participants, respectively. A history of mental disorders was associated with all four outcomes (P<0.05). Females gender and living with elderly and/or children were correlated with anxiety and PTSD (P<0.05). Working at COVID-19 front- and second-line hospitals were similarly linked to higher insomnia and PTSD levels (P<0.05). Also, working in COVID-19 wards or non-clinical settings was associated with anxiety and depression (P<0.05). Conclusion:Most of the HCWs in this study may experience mental difficulties. Some factors may increase their risk of experiencing these difficulties. Hence, in the crisis era, mental health monitoring and identification of groups with predisposing factors are required to provide appropriate care as quickly as feasible.